Expert opinion on the diagnostic odyssey and management of late-onset Pompe disease: a neurologist's perspective - Erdem Ozdamar, Sevim; Koc, Ayse Filiz; Durmus Tekce, Hacer; Kotan, Dilcan; Ekmekci, Ahmet Hakan; Sengun, Ihsan Sukru; Yuceyar, Ayse Nur; Uluc, Kayihan (Frontiers in Neurology, 2023)
This consensus statement by a panel of neurology experts aimed to provide a practical and implementable guidance document to assist clinicians for best clinical practice in terms of diagnosis, treatment and monitoring of late-onset Pompe disease (LOPD). The participating experts consider the clinical suspicion of LOPD by the physician to be of utmost importance in prevention of diagnostic and therapeutic delay in LOPD patients. A diagnostic algorithm is proposed to facilitate the diagnosis of LOPD in patients presenting with unexplained proximal/axial weakness (with or without respiratory symptoms) or restrictive respiratory insufficiency with hyperCKemia and/or exercise intolerance as the red flag symptoms/signs that raise index of suspicion for LOPD diagnosis. The diagnosis is based on subsequent use of dried blood spot (DBS) assay and the DBS assay can be confirmed by acid alpha-glucosidase (GAA) tissue analysis in leukocytes, fibroblasts, or muscle fibres and/or genetic mutation analysis. Accordingly, experts consider increased awareness among physicians about potential presenting characteristics with high index of suspicion for LOPD to be crucial to suspect and consider LOPD in the differential diagnosis, while strongly suggest the use of a diagnostic algorithm combined with DBS assay and confirmatory tests in timely diagnosis of LOPD and implementation of best practice patterns.